Unemployment dynamics and the Beveridge curve in Greece - Athanasios O. Tagkalakis (IZA Journal of European Labor Studies, 2016)
In this paper, we investigate the unemployment dynamics and the determinants of the Beveridge curve in Greece. The economic recession alongside labor market reforms raised the inflow rate to and decreased the outflow rate from unemployment in the early crisis years. The gradual normalization of economic conditions and the adoption of further structural reforms led to a decline in the inflow rate and an increase in the outflow rate. Our results are suggestive of the presence of an inverse relationship between unemployment and vacancies in Greece, which is driven by the post-crisis developments.
Keywords: J63; E32; J64; O52; 330; Unemployment; Inflow; Outflows; Beveridge; Reforms